Evaluasi Manfaat Penggunaan Aplikasi E-Mobile Posyandu Terhadap Kader Posyandu dalam Proyek Pos Pintar sebagai Program CSR The Hongkong and Shanghai Bank Corporation (HSBC) di Posyandu Pepaya, RW 16, Kecamatan Cilincing, Jakarta Utara. (Jurnal Ilmu Kesejahteraan Sosial, 2018)
The role of cadres is very important in improving posyandu services, therefore we need to strengthen the role of cadre as a source of health information and to encourage mothers with children under five years old to come to the posyandu. Through one of HSBC CSR programs called Pos Pintar Project, cadres are capacitated through the training of mobile-Posyandu applications so that they can provide better services to mothers with children under five years old who come to the posyandu. This study uses a qualitative approach with a type of summative evaluation research. The result shows that posyandu cadres who use mobile-Posyandu applications are more helpful when monitoring the child's growth and development. The result of the monitoring submitted into the application which faster than the manual method. This application also supports cadres in providing counseling for mothers with children under five years old. It helps mothers to understand the counseling given by the cadres easier, so that they practice how to give appropriate feeding to their children. Given this situation, the capacity improvement for posyandu cadre through CSR program needs to be scaled up. However, improvement needs to made is some areas such as advocacy to the local government, staff management, as well as resolve technical issues that often appears in the mobile-Posyandu application.